Respuesta :
Step-by-step explanation:
Subtract 2z2z from both sides of the equation.
x−2y+z=1x-2y+z=1
y=5−2zy=5-2z
x+y+3z=8x+y+3z=8
Replace all occurrences of yy with 5−2z5-2z in each equation.
x−2(5−2z)+z=1x-2(5-2z)+z=1
y=5−2zy=5-2z
x+5−2z+3z=8x+5-2z+3z=8
Simplify each equation.
x−10+5z=1x-10+5z=1
y=5−2zy=5-2z
x+5+z=8x+5+z=8
Move all terms not containing xx to the right side of the equation.
x=11−5zx=11-5z
y=5−2zy=5-2z
x+5+z=8x+5+z=8
Replace all occurrences of xx in x+5+z=8x+5+z=8 with 11−5z11-5z.
x=11−5zx=11-5z
y=5−2zy=5-2z
(11−5z)+5+z=8(11-5z)+5+z=8
Simplify (11−5z)+5+z(11-5z)+5+z.
x=11−5zx=11-5z
y=5−2zy=5-2z
−4z+16
Answer: (-9, 1, 4)
Step-by-step explanation:
its right on acellus